Analysis of the collision between top tensioned risers - Lim, Zhen Xun. (2012)
Increasingly, the world is facing increasing demand for oil and gas. To satisfy this hunger for biofuels, and solve decreasing supply in current oil fields, the industry is looking to exploration of deeper seas. In an offshore platform, the riser has become a standard, tunneling deep sea deposits to shore. With deeper waters, these risers are more prone to collision. Thus, there is an urgent need to explore different factors that will affect these tensioned risers.